IMPLEMENTASI PENGATUR KECEPATAN MOTOR PADA MESIN CONVEYOR PENYORTIR LOGAM OTOMATIS - Mindit Eriyadi; Indra Maryana Lesmana Putra (Jurnal Teknologi Terapan, 2020)
Metal sorting conveyor is a device that is used to separate metal and non-metal objects, the drive of this conveyor uses ½ Horse Power (HP) induction motor as its prime mover. To adjust the rotation of the induction motor 1 HP Variable Frequency Drive (VFD) is used. This VFD is set with the double speed parameter so that later the motor can rotate variably in two speeds. The input parameters of the VFD itself use switches in the form of photo electric and inductive proximity which are controlled automatically using Programmable Logic Control (PLC). The digital output of the PLC will then communicate with the digital input of the VFD so that when the object on the conveyor is detected by a photoelectric, the VFD will adjust the frequency by 8,5 Hz, if the object on the conveyor is detected by metal by inductive proximity, the VFD will set the frequency by 14,5Hz . So that at each of these frequencies the motor can rotate with speeds of 241,5 rpm and 359,5 rpm. The results of the trials carried out show that VFD can regulate in a number of speeds in a variable manner, but in this study limited to using two speeds or double speed as a variable speed experiment.